Measurement of Satellite Solar Array Panel Vibrations Caused by Thermal Snap and Gas Jet Thruster Firing - Oda, Mitsushige; Hagiwara, Yusuke; Suzuki, Satoshi; Nakamura, Toshiyuki; Inaba, Noriyasu; Sawada, Hirotaka; Yoshii, Masahiro; Goto, Naoki (IntechOpen, 2011)
None